Myotendinous junction adaptations to ladder-based resistance training: identification of a new telocyte niche - Pimentel Neto, Jurandyr [UNESP]; Rocha, Lara Caetano [UNESP]; Barbosa, Gabriela Klein [UNESP]; Jacob, Carolina dos Santos [UNESP]; Krause Neto, Walter; Watanabe, Ii-sei; Ciena, Adriano Polican [UNESP] (Springer Nature, 2020)
The present study shows chronic adjustments in the myotendinous junction (MTJ) in response to different ladder-based resistance training (LRT) protocols. Thirty adult male Wistar rats were divided into groups: sedentary (S), calisthenics (LRT without additional load [C]), and resistance-trained (LRT with extra weight [R]). We demonstrated longer lengths of sarcoplasmatic invaginations in the trained groups; however, evaginations were seen mainly in group R. We showed a greater thickness of sarcoplasmatic invaginations in groups C and R, in addition to greater evaginations in R. We also observed thinner basal lamina in trained groups. The support collagen layer (SCL) adjacent to the MTJ and the diameters of the transverse fibrils were larger in R. We also discovered a niche of telocytes in the MTJ with electron micrographs of the plantar muscle and with immunostaining with CD34+ in the gastrocnemius muscle near the blood vessels and pericytes. We concluded that the continuous adjustments in the MTJ ultrastructure were the result of tissue plasticity induced by LRT, which is causally related to muscle hypertrophy and, consequently, to the remodeling of the contact interface. Also, we reveal the existence of a collagen layer adjacent to MTJ and discover a new micro anatomic location of telocytes.